Impact of Stress on Humans and Its Detection Using Artificial Intelligence - Paul, Hrithick; Mishra, Nirbhay; Ghatak, Sayani; Singh, Dhararmpal; Ghosh, Debmitra; Singha, Pratyush (International Journal of Computer Sciences and Engineering, 2026)
Stress is our body's emotional and physical reaction to a circumstance or event that we perceive as risky or difficult. Different levels of stress are experienced by people on a regular basis, which causes serious problems. Three main types of stress are acute stress, episodic stress, and chronic stress. A new or challenging situation generates acute stress in your body. It's the emotion people experience as a deadline approaches or when they just miss getting hit by a car. We might even come across it as a result of a fun pastime. Like an exciting ride on a roller coaster or a stunning feat of personal achievement. Acute stress is a category for short-term stress. After a little period of time, the body and emotions usually return to normal. Then comes Continual acute pressures are referred to as episodic acute stresses. The cause of this can be persistently tight job deadlines. It might also be due to the frequent high-stress situations that some professions face. Long-lasting demands are ultimately what lead to chronic stress. One example is living in a high-crime area or constantly fighting with your significant other. These health issues have all been related to the onset of stress, dilated pupils, increased heart rate, anxiety, mood swings, lack of sleep, weight gain, insomnia, panic attacks, persistent headaches, and other variables. So, the stress management system will offer a technique of management from which we can identify the level of stress or kinds of stress and offer solutions for how we can lower the tension and release people from this type of stress.